Winds at the Mars 2020 Landing Site. 2. Wind Variability and Turbulence. Issue 12 (21st December 2022) - Viúdez‐Moreiras, D.; de la Torre, M.; Gómez‐Elvira, J.; Lorenz, R. D.; Apéstigue, V.; Guzewich, S.; Mischna, M.; Sullivan, R.; Herkenhoff, K.; Toledo, D.; Lemmon, M.; Smith, M.; et al.
Abstract: Wind speeds measured by the Mars 2020 Perseverance rover in Jezero crater were fitted as a Weibull distribution. InSight wind data acquired in Elysium Planitia were also used to contextualize observations. Jezero winds were found to be much calmer on average than in previous landing sites, despite the intense aeolian activity observed. However, a great influence of turbulence and wave activity was observed in the wind speed variations, thus driving the probability of reaching the highest wind speeds at Jezero, instead of sustained winds driven by local, regional, or large‐scale circulation. The power spectral density of wind speed fluctuations follows a power‐law, whose slope deviates depending on the time of day from that predicted considering homogeneous and isotropic turbulence. Daytime wave activity is related to convection cells and smaller eddies in the boundary layer, advected over the crater. The signature of convection cells was also found during dust storm conditions, when prevailing winds were consistent with a tidal drive. Nighttime fluctuations were also intense, suggesting strong mechanical turbulence. Convective vortices were usually involved in rapid wind fluctuations and extreme winds, with variations peaking at 9.2 times the background winds. Transient high wind events by vortex‐passages, turbulence, and wave activity could be driving aeolian activity at Jezero. We report the detection of a strong dust cloud of 0.75–1.5 km in length passing over the rover. The observed aeolian activity had major implications for instrumentation, with the wind sensor suffering damage throughout the mission, probably due to flying debris advected by winds. Plain Language Summary: Jezero winds as measured in the crater floor by Perseverance were found to be much calmer on average than in previous landing sites. Turbulence and wave activity provoked rapid fluctuations that changed wind speed from calm conditions to more than 10–15 ms −1 in the timescale of seconds to minutes. Daytime wave activity is related to convection cells and smaller eddies in the boundary layer, advected over the crater. These convection cells are produced under strong thermal gradients typically present during daytime. Pressure drops, associated with convective vortices, were usually involved in rapid wind fluctuations and, in some cases, in extreme winds as measured by Perseverance. An intense aeolian activity was observed at Jezero crater produced by transient high wind events. This aeolian activity had major implications for instrumentation, with the Perseverance wind sensor suffering damage probably due to flying debris advected by winds. Also, we report the detection of a strong dust cloud of 0.75–1.5 km passing over the rover. This paper has a companion paper (part 1) in the same issue, which is focused on wind patterns and analyzed the mechanisms driving atmospheric circulation at Jezero. Key Points: Jezero winds are found to be much calmer on average than in previous landing sites, despite the intense aeolian activity observed Turbulence, wave activity, and convective vortices drive the peak wind speeds observed at Jezero We report the detection of a dust cloud of 0.75–1.5 km in length passing over the rover